Overexpression of a glycogenin, CmGLG2, enhances floridean starch accumulation in the red alga Cyanidioschyzon merolae. (3rd June 2019) - Pancha, Imran; Tanaka, Kan; Imamura, Sousuke
ABSTRACT: Microalgae accumulate energy-reserved molecules, such as triacylglycerol and carbohydrates, which are suitable feedstocks for renewable energies such as biodiesel and bioethanol. However, the molecular mechanisms behind the microalgae accumulating these molecules require further elucidation. Recently, we have reported that the target of rapamycin (TOR)-signaling is a major pathway to regulate floridean starch synthesis by changing the phosphorylation status of CmGLG1, a glycogenin generally required for the initiation of starch/glycogen synthesis, in the unicellular red alga Cyanidioschyzon merolae . In the present study, we confirmed that another glycogenin, CmGLG2, is also involved in the floridean starch synthesis in this alga, since the CmGLG2 overexpression resulted in a two-fold higher floridean starch content in the cell. The results indicate that both glycogenin isoforms play an important role in floridean starch synthesis in C. merolae, and would be a potential target for improvement of floridean starch production in microalgae.